Ответ:
-1
Пошаговое объяснение:
2(6х + 10) – 2 = 2х +8
12x+20-2=2x+8
12x+18=2x+8 |-8
12x+10=2x |-2x
10x+10=0 |-10
10x=-10 |:10
x=-1
Ответ: 12х+20-2=2х+8
12х+18=2х+8)(12х-2х)+18=(2х-2х)+8
10х+18=8
10х+(18-18)=8-18
10х=8-18
10х= -10
10х/10=-10\10 (это дробь)
10\10=1
х=-10\10
-10\10=10(-1)\10*1=10\10х-1= -1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-1
Пошаговое объяснение:
2(6х + 10) – 2 = 2х +8
12x+20-2=2x+8
12x+18=2x+8 |-8
12x+10=2x |-2x
10x+10=0 |-10
10x=-10 |:10
x=-1
Ответ: 12х+20-2=2х+8
12х+18=2х+8)(12х-2х)+18=(2х-2х)+8
10х+18=8
10х+(18-18)=8-18
10х=8-18
10х= -10
10х/10=-10\10 (это дробь)
10\10=1
х=-10\10
-10\10=10(-1)\10*1=10\10х-1= -1